Islamic Law View on Standard Education Expenses as Child Support: Case Study of Migrant Families in Klakah, Lumajang Regency - Fathul Ulum (STAI Syaichona Moh. Cholil Bangkalan, 2023)
This study examines the Islamic standard for educational costs as child support for migrant families in Klakah Village, Lumajang Regency. This research approach implemented a qualitative approach with an empirical juridical design. Data were obtained from five informants whose husbands were currently living away from home. Data collection techniques used interviews, observation, and documentation. The results showed that two families were not yet fully aware of their responsibility for providing for their children's education, and three families were still fulfilling their responsibilities to cover their children's education costs. The reason for not meeting educational costs was the family's focus on building a house and paying off debts. Parents recognized the importance of balancing material and religious aspects in child rearing. Keywords: Educational costs, child support, Islamic law